ANALISIS MODE SISTEM PEMBANGKIT HYBRID BERKELANJUTAN PLTMH-PLN DENGAN SOLAR CELL MENGGUNAKAN HELIOSCOPE DAN HOMER - Sepannur Bandri; Rafika Andari; Liliana Liliana; Rendisky Rendisky (Sekolah Tinggi Teknologi Industri Padang, 2022)
This study aims to examine the total cost savings of PLN's electricity bill, which is quite high during the dry season, by using solar panels on a building's roof. The study took place at the PTPN VI Kayu Aro Tea Factory in Kerinci Regency, Jambi Province. Because using renewable energy sources is more complicated than using Microhydro resources, a Hybrid Optimization Model of Electric Renewable (HOMER) application program is required. This application program is used to determine the lowest Initial Cost, Cost Of Energy (COE), and Break Event Point (BEP) over a 25-year period. The Helioscope allows us to identify the required components, which are 164 330 wp solar panels, 2 Surette Rolls 4-Ks25p batteries, and 1 40000TL3-S hybrid inverter. According to the Hybrid Optimization Model of Electric Renewable (HOMER) analysis, the initial cost is IDR 1,049,620,000, the Cost of Energy (COE) is IDR 752/Kwh, and the Break Event Point (BEP) is for 24 years. The simulation results from optimizing the design of the Hybrid microhydro system, PLN with a continuous photovoltaic array show that the contribution of electrical energy produced by PLN is 11,856 kWh/year (16.3%) and solar cells is PV: 61,092 kWh/year (83.7%).